2017
DOI: 10.1089/wound.2017.0730
|View full text |Cite
|
Sign up to set email alerts
|

Fournier's Gangrene: A Review and Outcome Comparison from 2009 to 2016

Abstract: Objective: The outcome of Fournier's gangrene (FG) may be affected by comorbidities, demographics, and choice of treatment modality. We sought to evaluate our institution's management protocol of FG measured by mortality rate (MR) and length of hospital stay (LHS) in a retrospective cohort study. Approach: A database of 20 FG cases at our institution throughout the 2009-2016 study period was assembled by a retrospective review of medical records. A Fournier's Gangrene Severity Index Score (FGSIS) was calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 17 publications
(35 reference statements)
1
23
0
8
Order By: Relevance
“…The authors from urology clinics reported the rate of females as 0-5% in their studies. [5,10] In contrast, studies from the other clinics reported that the female patients composed 56% and 28.8% of the whole patients. [9,11] In our study, the mean age of the patients was 59 years, and 97% of the patients were male.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The authors from urology clinics reported the rate of females as 0-5% in their studies. [5,10] In contrast, studies from the other clinics reported that the female patients composed 56% and 28.8% of the whole patients. [9,11] In our study, the mean age of the patients was 59 years, and 97% of the patients were male.…”
Section: Discussionmentioning
confidence: 87%
“…[4] Since this description of Fournier, the classical patient profile has been changed. [5] Fournier's gangrene has been shown to be associated with several comorbidities and affects both genders, either young patients or elder ones as well.…”
mentioning
confidence: 99%
“…The mortality rates decreased after the early diagnosis of FG and treatment with more radical methods, and the main concern became prolonged LOS [5]. There are studies reporting that numerous parameters such as increased age, BMI, smo-▶ king, presence of comorbidity, FGSI score, urinary or fecal diversion, use of HBOT and NPWT are significant for mortality [5,23,24]. In a 43,146 series scan, Furr et al found that the most important predictors of LOS were complex wound repair and urinary or fecal diversion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Based on 20 FG cases at their institution, Ferretti et al . reported the possibility of decreased hospital stays in FG patients treated with HBO . The two studies described above usually had standard management, such as administration of broad‐spectrum antibiotics and prompt surgical debridement.…”
Section: Fgmentioning
confidence: 99%